The multiple nutrition properties of some exotic fruits: Biological activity and active metabolites - Dembitsky V. (2017)
The main objective of this review was to describe the physicochemical and nutritional characteristics of twenty selected exotic fruits and the influence of their physiologically active compounds on human health, through scientifically proven information. The review presents the biologically active metabolites derived from exotic fruits (polyphenols, flavonoids, flavanols, tannins, ascorbic acid, anthocyanins, volatile compounds, minerals, and organic acids) and various analytical methods for their detection (elemental analysis, electrophoretic separation by SDS-polyacrylamide gel electrophoresis, and fast protein liquid and ion-exchange chromatography; GC-MS, HPLC/diode array detection (DAD), circular dichroism (CD), differential scanning calorimetry (DSC), Fourier transform infrared (FT-IR), ultraviolet spectroscopy, two- and three-dimensional fluorimetry (2D-FL) and (3D-FL), and antioxidant radical scavenging assays (DPPH, FRAP, CUPRAC, ABTS, and ORAC). The correlation between the polyphenols and other bioactive compounds, and their antioxidant activities was reported for different fruit extracts. During the last two decades our international scientific group investigated in vitro the physicochemical and nutritional characteristics of avocado, dragon fruit, durian, kiwifruit, mango, mangosteen, persimmon and snake fruit, and in vivo their influence on laboratory animals and humans. Supplementation of diets with exotic fruits positively affects plasma lipid profile, antioxidant activity and histological examination of aorta in rats fed cholesterol-containing diets. The interaction between drugs and serum albumin plays an important role in the distribution and metabolism of drugs. The properties of polyphenol methanol extracts of exotic fruits showed the ability to quench serum albumin by forming the complexes similar with the ones between proteins and pure flavonoids. Our experimental data and a wide range of other investigations are included in this review. In conclusion, it is nessasary to promote a consumption of exotic fruits (a rich source of natural antioxidants) as a supplement to everyday human diet. © 2011 Elsevier Ltd.